Perceived social support and quality of life in endometrial cancer patients: a longitudinal study - Mandato, Vincenzo Dario; Paterlini, Marcella; Torricelli, Federica; Rabitti, Elisa; Mastrofilippo, Valentina; Aguzzoli, Lorenzo (Frontiers in Oncology, 2024)
Objective: This study aimed to assess the influence of medical history, perceived physician-patient communication, and perceived social support on changes in the quality of life (QoL) during the first year of follow-up in patients undergoing surgery for endometrial cancer (EC), the most prevalent gynecological cancer in Western countries, especially in Central and Eastern Europe and North America. Methods: This prospective longitudinal study included 98 EC patients. All participants completed the Short Form 36 (SF-36) and the Multidimensional Scale of Perceived Social Support (MSPSS) one month and one year after surgery. Additionally, one month after surgery, they responded to a questionnaire designed by the researchers concerning the key aspects of physician-patient communication. Results: Our findings revealed that patients reporting high social support one month after surgery demonstrated significantly improved emotional well-being (EWB) at both one month and one year after the surgery, with statistically significant higher scores in the dimension of EWB (p<0.05). The support from a significant other at one year correlates with greater PF (p<0.005), fewer limitations due to physical health (p<0.05), less pain (p<0.05), less fatigue (p<0.05), and better general and EWB (p<0.05). Conclusions: This study underscores the significance of perceived social support for patients cross endometrial cancer. The multifaceted nature of social support, encompassing emotional assistance and information sharing, emerges as a pivotal factor aiding patients in confronting the challenges inherent to EC. This form of support contributes to bolstering psychological well-being and enhancing overall QoL.